Seroprevalence of Toxoplasma Antibody in a Toronto Population. (1996) - Ford-Jones, EL; Kitai, I; Corey, M; Notenboom, R; Hollander, N; Kelly, E; Akoury, H; Ryan, G; Kyle, I; Gold, R
Abstract : OBJECTIVE: To determine the prevalence of infection with toxoplasmosis by country of birth and age in a sample of convenience. DESIGN: Banked sera and the computerized data base of demographic and other factors from an earlier epidemiological study were retrieved. SETTING: Thirty-eight infant-toddler day care centres in Toronto. POPULATION: Day care providers from whom informed consent was obtained and banked sera were available. MAIN RESULTS: Of the 124 providers whose serum was tested, 16 (12.9%) were seropositive. Of those providers born in Canada, 8.2% were seropositive, while of those born outside of Canada, 19.6% were positive (P=0.067, OR 2.68, 95% CI 0.91, 7.94). While there was no significant association of seropositivity with age, the association of seropositivity with country of birth was different in the providers under 30 years of age. Among those born in Canada, 4.6% were seropositive, while among those born outside of Canada 23.1% were seropositive. CONCLUSIONS: The data supplement the limited existing data on toxoplasmosis infection in Canada. Among Canadians, those born outside of Canada were more likely to be seropositive than those born in Canada, suggesting that there may be a differential risk of congenital infection for infants whose parents were born outside of Canada.